Impact of Diagnostic Delay and Associated Factors on Clinical Outcomes in a U.S. Inflammatory Bowel Disease Cohort. Issue 10 (October 2017) - Nguyen, Vu Q.; Jiang, Dingfeng; Hoffman, Sharon N.; Guntaka, Srikar; Mays, Jessica L.; Wang, Anthony; Gomes, Joseph; Sorrentino, Dario
Abstract : Background: The impact of diagnostic delay in inflammatory bowel disease, including Crohn's disease (CD) and ulcerative colitis (UC), on disease course remains uncertain. This study examines factors that may influence time to diagnosis and disease outcomes in a U.S. patient cohort. Methods: We retrospectively collected data on patient characteristics, time to diagnosis, disease phenotype, and complications in 177 patients with inflammatory bowel disease (110 CD and 67 UC) diagnosed at our institution from 2008 to 2015. Factors potentially affecting time to diagnosis were analyzed. Association between disease complications (perianal disease, intestinal strictures, surgery, fistula, abscess, and perforation) and time to diagnosis was tested by multivariable analysis. Results: The median time to diagnosis was longer for patients with CD compared with patients with UC (median 9.5 versus 3.1 months; P < 0.001). The median time from symptom onset to initial physician visit was similar for patients with CD and patients with UC (1 month). However, the median time from symptom onset to specialist evaluation was longer for patients with CD compared with patients with UC: 7 months (interquartile range: 3–23) versus 3 months (interquartile range: 1–8), respectively ( P < 0.001). In CD, ileal disease and hematochezia were positively and negatively correlated, respectively, with longer time to diagnosis ( P < 0.05). Compared with patients with time to diagnosis ⩽4 months, patients with time >26 months had increased overall complications (odds ratio, 8.22; P = 0.007) and intestinal strictures (odds ratio, 8.96; P = 0.012) at time of diagnosis. Such correlation persisted at follow-up. Conclusions: Time to diagnosis was long in CD. Physician-related delay in diagnosing CD was associated with increased overall complications and intestinal strictures (See Video Abstract, Supplemental Digital Content 1, http://links.lww.com/IBD/B646 ). Abstract : Supplemental Digital Content is Available in the Text.Article first published online 7 September 2017.